Case Report: Clinical and Genetic Characteristics of Pearson Syndrome in a Chinese Boy and 139 Patients - Ying, Yanqin; Liang, Yan; Luo, Xiaoping; Wei, Ming (Frontiers in Genetics, 2022)
Background: Pearson’s syndrome (PS) is a rare multi-system disorder caused by mitochondrial DNA deletion. Most PS cases in the literature are individual reports, and there is a lack of systematic analysis of clinical features and gene mutations in large samples. Objective: To report a case of PS and summarize the clinical features and genetic characteristics of PS by reviewing the literature. Methods: We reported a case of PS in a boy with severe anemia and multi-system disorder. Genetic etiology was identified by mitochondrial DNA sequencing and whole-exon sequencing. Clinical features and gene mutations were summarized by literature review. Results: The patient had major clinical manifestations with recurrent anemia and multiple organ failure after infection. Mitochondrial DNA sequencing revealed a de novo heteroplasmic deletion of 3.063 kb (nt 6,224–9,287) with 75% heteroplasmy in peripheral blood. A total of 139 PS cases were retrieved after a literature search. The most common initial symptom was refractory anemia requiring repeated blood transfusion (86.2%), digestive system symptoms (26.9%), and failure to thrive (15.4%). During the course of disease, the observed symptoms were bone marrow failure (100%), metabolic disorders (61.87%) and gastrointestinal symptoms (61.87%), failure to thrive (48.9%), renal disorders (42.45%), and pancreatic exocrine insufficiency (39.6%). The mean heteroplasmy of mitochondrial DNA mutation in peripheral blood in deaths (76.29 ± 11.86%, n = 29) was higher than that in survivals (59.92 ± 23.87%, n = 26, p < 0.01). Among the patients with the 4.977 kb deletion, the heteroplasmy in peripheral blood in deaths (79.64 ± 9.71%, n = 11) was higher than that in survivals (56.67 ± 27.65%, n = 9, p < 0.05). Conclusion: PS can affect multiple systems, and mitochondrial DNA sequencing should be performed early. The heteroplasmy in peripheral blood is related to prognosis.